Longitudinal Development of Health-related Quality of Life and Fatigue in Children on Home Parenteral Nutrition. Issue 1 (January 2022) - Nagelkerke, Sjoerd C.J.; van Oers, Hedy A.; Haverman, Lotte; Vlug, Lotte E.; de Koning, Barbara A.E.; Benninga, Marc A.; Tabbers, Merit M.
ABSTRACT: Objectives: The aim of the study was to describe the longitudinal development of health-related quality of life (HRQOL) and fatigue in children with chronic intestinal failure (CIF) on home parenteral nutrition (PN) and compare these children to the general population. Methods: Prospective, observational study conducted over 7 years in patients suffering from CIF receiving home PN from 2 tertiary hospitals in the Netherlands. Every 6 months, parents (if child <8 years old) or patients (if child ≥8 years old) completed 2 questionnaires: Pediatric Quality of Life Inventory 4.0 (PedsQL) Generic and Fatigue on the KLIK (kwaliteit van leven in kaart [Dutch Acronym for Quality of Life in Clinical Practice]) Patient Reported Outcome Measures portal, which were compared with the general population. Linear mixed models (LMMs) were constructed to investigate the course of HRQOL over time. Results: Thirty-five patients were included (40% girls). At time of last KLIK contact, patients received HPN for a median of 5.3 years (interquartile range [IQR]: 2.9–9.7). In total, 272 questionnaires were completed. PedsQL generic total score for ages 5 to 7 and 8 to 12 years was significantly lower than the general population ( P < 0.01 for both age groups) with effect sizes of 0.73 and 0.71, respectively. PedsQL fatigue total score for ages 5 to 7 years was also significantly lower ( P = 0.01; effect size 0.70). LMMs for PedsQL Generic and Fatigue total score 2 to 7 and 8 to 18 years showed no significant coefficient for duration of home PN. Conclusions: Children suffering from CIF receiving home PN ages 5 to 12 years report lower HRQOL scores than the general population. HRQOL and fatigue do not change during long-term treatment with home PN in these children. Abstract : Supplemental Digital Content is available in the text